1987
DOI: 10.1128/jb.169.10.4750-4758.1987
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically resolved states of the Halobacterium halobium flagellar motor switch and modulation of the switch by sensory rhodopsin I

Abstract: Spontaneous switching of the rotation sense of the flagellar motor of the archaebacterium Halobacterium halobium and modulation of the switch by attractant and repellent photostimuli were analyzed by using a computerized cell-tracking system with 67-ms resolution coupled to electronic shutters. The data fit a three-state model of the switch, in which a Poisson process governs the transition from state N (nonreversing) to state R (reversing). After a reversal, the switch returns to state N, passing through an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 35 publications
(47 reference statements)
2
45
0
Order By: Relevance
“…1A), in accordance with previous results (10,15). Almost all cells reversed their swimming direction 2 to…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…1A), in accordance with previous results (10,15). Almost all cells reversed their swimming direction 2 to…”
Section: Resultssupporting
confidence: 81%
“…However, this response fails to occur if the stimulus is applied during the first half-second after a reversal has taken place, during the so-called refractory period. Cells regain responsiveness within the following 2 s (10,15).…”
mentioning
confidence: 99%
“…Given the exponential decay of the frequency distribution, we suggested spontaneous motor switching to be a stochastic event and introduced a four-state model of the flagellar motor switch sufficient to fit the experimental data quantitatively (21). Both the exponential decay and the interpretation of motor switching as a stochastic event were confirmed by McCain et al, who in addition showed that the length of a given swimming interval is independent of the length of the preceding one (24). In this context, it is of interest that a four-state model has also been proposed for the motor switch in E. coli (12) and that threshold crossings of a regulatory substance subjected to statistical fluctuations have been excluded from causing spontaneous motor switching (5).…”
Section: Discussionmentioning
confidence: 50%
“…The exponential decay of the frequency distribution for flagellar reversal was taken as evidence that the spontaneous motor switching is a stochastic rather than an oscillator-mediated event (Marwan et al, 1991). The interval distribution could be fitted either to a symmetric four-state model (Marwan and Oesterhelt, 1987) or an asymmetric three-state model (McCain et al, 1987) of the flagellar switch. Such models have also been proposed for the chemotactic behavior of Salmonella typhimurium (Kuo and Koshland, 1989).…”
Section: Effector Adaptationmentioning
confidence: 99%